Pengaruh Model Pembelajaran Problem Solving dan Kemampuan Numerik Terhadap Penguasaan Literasi Matematika Di SMP - Buyung - (JTP - Jurnal Teknologi Pendidikan, 2014)
The aims of this research is to know in uence the instructional model and numeri- cal ability to mathematical literacy mastery. Research method is quasi-experimental disign with treatmen by level 2 X 2. Data was collected with mathematical literasi mastery test. The result of this research shows that: in total mathematical literacy mastery of students who use problem solving model were higher than those conventional model. There were several interaction effects between the instructional model with numerical ability toward the students’ mathematical literacy mastery. The students with higher numerical ability achieved higher mathematical literacy mastery by using problem solving model than those conventional model. The students with lower numerical ability achieved mathematical lit- eracy mastery by using problem solving model as same as conventional model.